Understanding semiconductor devices - Dimitrijev, Sima, 1958- (The Oxford series in electrical and computer engineering, 2000)
Ideal for undergraduate and beginning graduate students in electrical engineering, Understanding Semiconductor Devices provides a solid grounding in both fundamental principles and practical skills. The text features intuitive explanations and a motivating "electronics-to-physics" approach that progresses from basic to more abstract concepts. It includes intriguing and diverse problems, review questions, and worked out examples.